Ruminant grazing feeding and methane production - Vergara-López, Juan (Revista de la Facultad de Agronomía de la Universidad del Zulia, 2023)
Climate change limits the release of radiation from the earth's atmosphere, a product of the accumulation of greenhouse gases (GHG) such as CO2, methane, ammonia, among others. Ruminants contribute methane to the atmosphere when fed with low quality forage diets, which in the light of different conservationist organizations, qualifies them as major pollutants. When Venezuela signed the Kyoto Protocol in 2004, it undertook to establish a GHG measurement system, as well as scientific research on the subject; however, there are still no research groups in the country dedicated to the permanent measurement of GHG contributions from these production systems. Grazing pastures and forages of medium to low quality, with high contents of cell wall of low degradability, produce a positive balance towards the generation of methane of enteric origin, which could be mitigated if these feeding schemes are improved, tending to improve the digestibility of basic diets. Methane production by these production systems in the state of Zulia is calculated at 209 Gg, 7.1 % of the total inventoried at the national level; however, the lack of research in this area, as well as of systematic inventories of local herds, prevents obtaining accurate data in this regard.